PERAN KELOMPOK TANI MANGKU ALAM DALAM MENSEJAHTERAKAN MASYARAKAT MELALUI PROGRAM PERKEBUNAN CENGKIH DI DESA PAGERSARI KECAMATAN BERGAS KABUPATEN SEMARANG - Purnomo, Annida Zulfatus Saniyyah (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research examines the role of the Mangku Alam Farmers Group in Pagersari Village, Bergas District, Semarang Regency in improving community welfare through the clove plantation program. This farmer group was formed as a solution to the problems faced by farmers, such as the scarcity of fertilizer and low selling prices for their crops. With a qualitative approach, this research uses interview, observation and documentation methods.   The research results show that the Mangku Alam Farmers Group not only acts as a forum for empowering farmers through training and providing agricultural facilities, but also succeeds in increasing the income and standard of living of its members. Programs such as making organic fertilizer and planting cloves have a positive impact on the community's economy and foster a spirit of togetherness and mutual cooperation. This research emphasizes the importance of organizing farmer groups in solving poverty problems at the local level.